Burgos Wind Farm Project : The Philippines Technical Desk Review - Cronin, Tom; Clausen, Niels-Erik; Nielsen, Morten; Jørgensen, Erik (World Bank, Washington, DC, 2013)
This report presents the findings of a review carried out by Riso National Laboratory of a 30MW wind farm in Northern Luzon, The Philippines. The review was commissioned by the World Bank and is intended as a brief second opinion desk review of the technical, contractual and financial aspects of the project. The evaluation of the Annual Energy Production of the site by PNOC-EDC seems to follow accepted practice and where shortcomings have been found by the review, it is considered that their correction would not change the outcome significantly. For example, only data from one year has been used but the review has found that it is probably unnecessary to correct the data for long term deviations, having looked at historical data from other sources. Two wind turbine layouts were assessed and it was seen that, apart from some minor adjustments, the layout is more or less optimal. The precise layout and optimization will, in any case, be done by the contractor.